Potentially avoidable hospitalizations among Medicare beneficiaries with Alzheimer's disease and related disorders. Issue 1 (1st January 2013) - Lin, Pei‐Jung; Fillit, Howard M.; Cohen, Joshua T.; Neumann, Peter J.
Abstract : Background: Individuals with Alzheimer's disease and related disorders (ADRD) have more frequent hospitalizations than individuals without ADRD, and some of these admissions may be preventable with proactive outpatient care. Methods: This study was a cross‐sectional analysis of Medicare claims data from 195, 024 fee‐for‐service ADRD beneficiaries aged ≥65 years and an equal number of matched non‐ADRD controls drawn from the 5% random sample of Medicare beneficiaries in 2007–2008. We analyzed the proportion of patients with potentially avoidable hospitalizations (PAHs, as defined by the Medicare Ambulatory Care Indicators for the Elderly) and used logistic regression to examine patient characteristics associated with PAHs. We used paired t tests to compare Medicare expenditures by ADRD status, stratified by whether there were PAHs related to a particular condition. Results: Compared with matched non‐ADRD subjects, Medicare beneficiaries with ADRD were significantly more likely to have PAHs for diabetes short‐term complications (OR = 1.43; 95% CI 1.31–1.57), diabetes long‐term complications (OR = 1.08; 95% CI = 1.02–1.14), and hypertension (OR = 1.22; 95% CI 1.08–1.38), but less likely to have PAHs for chronic obstructive pulmonary disease (COPD)/asthma (OR = 0.85; 95% CI 0.82–0.87) and heart failure (OR = 0.89; 95% CI 0.86–0.92). Risks of PAHs increased significantly with comorbidity burden. Among beneficiaries with a PAH, total Medicare expenditures were significantly higher for those subjects who also had ADRD. Conclusion: Medicare beneficiaries with ADRD were at a higher risk of PAHs for certain uncontrolled comorbidities and incurred higher Medicare expenditures compared with matched controls without dementia. ADRD appears to make the management of some comorbidities more difficult and expensive. Ideally, ADRD programs should involve care management targeting high‐risk patients with multiple chronic conditions.